The Meaning of the Gecko Motif on Utan Welak Woven Cloth from Maumere (Oratio Directa, 2020)
The gecko motif on Utan Welak woven cloth functions as a communication symbol in the tradition of the Krowe-Iwan Gete indigenous community in Sikka Regency, Flores, East Nusa Tenggara. This study examines the motif's denotative, connotative, and mythical meanings using Roland Barthes' semiotics. It applies a qualitative approach through observation at a weaving studio, interviews with the studio owners, and a literature review. Source triangulation was used to assess data validity. The findings show that, denotatively, the motif depicts a gecko in predominantly black and white. Connotatively, it signifies good fortune, permanence, and the continuity of ancestral heritage. At the level of myth, the gecko is understood as a magical symbol associated with ancestral spirits; consequently, the cloth is regarded as sacred and is worn by particular members of the community.
Keywords: Roland Barthes semiotics; Gecko motif; Utan Welak weaving; Sikka culture; Communication symbol